Characteristics of Se’i (Rotenesse Smoked Meat) Treated with Coconut Shell Liquid Smoked and Citrus aurantifolia Extract - Gemini E.M. Malelak; G.M. Sipahelut; I.G.N. Jelantik; M.R. Deno Ratu; H.J.D. Lalel (Faculty of Animal Science, Bogor Agricultural University, 2015)
The objective of this study was to investigate the effect of Citrus aurantifolia extract (CAE), coconut shell liquid smoke (CSLS) and the combination of CAE and CSLS (CACS) on se’i characteristics. A completely randomized design was assigned in this experiment. Treatments used were: se’i treated with 5% (v/v) CAE, CSLS 5% (v/v), (CAE : CSL 1:1) )/ (CACS) and untreated se’i as a control (C). Parameters measured were: aroma, color, taste, pH, residual nitrite, total bacterial count, Coliform, Staphylococcus aureus, Escherichia coli, and Salmonella. The data of aroma, color, and taste were analyzed by using Kruskal-Wallis test followed by Mann-Whitney test. The pH, residual nitrite, and bacterial data were analyzed with analysis of variance (ANOVA) followed by least significant differences test. Results showed that CAE caused the highest score at both aroma and taste (P<0.05). CSLS caused the lowest residual nitrite (27 ppm) (P<0.05). Application of CAE and CACS could reduce total bacteria (P<0.05) at least 1 log. Color, pH, and Coliform number were not significantly different. S. aureus, E. coli, and Salmonella were negative in all se’i samples. CAE gives the best organoleptics and bacteriological characteristics while CSLS is more effective in reducing nitrite.Key words: Citrus aurantifolia extract, coconut shell liquid smoke, se’i, smoked beef